BUDIDAYA STROWBERI SECARA HIDROPONIK DI ROOFTOP GEDUNG MERAH DENGAN PENGENDALIAN LINGKUNGAN SISTEM MOBILE PHONE - Daryono Daryono; Nur Hidayat; Rusmini Rusmini; Yuanita Yuanita; Eko Junirianto; Hamka Hamka; Eva Nurmarini (JURNAL AGRIMENT, 2021)
The hydroponic system can be a solution for the development of fruit and vegetable crops with various advantages over conventional agricultural systems, where nutritional needs and the growing environment (microclimate) can be manipulated using appropriate technology so that plants can grow optimally.Objective Measuring the success of hydroponics with a remote control system for regulating light intensity, humidity and temperature on the microclimate scale on hydroponic plants and comparing strawberry plants treated with microclimate settings without treatment, by making a cover shade and humidifier with an automation system and temperature sensor. This research was conducted at the Rooftop of Gedung Merah Politani Samarinda for 1 year starting from January 2020 to December 2020. This study used a completely randomized non-factorial one-factor 2-level treatment design, namely P1 = strawberry cultivation with shade treatment and humidifier P2 = strawberry cultivation without microclimate treatment (shade and humidifier). Each treatment level was repeated as many as 20 plants so that the total plants used in this study were 40 plants.The results of this study were the increase in the number of leaves of strawberry plants aged 8 weeks after planting, the highest average was in treatment P1, namely 8.55 cm and the lowest average of strawberry plants in treatment P2 was 6.50, and the increase in the number of leaves of strawberry plants aged 12 weeks after planting, the highest average was at P1, namely 13.7 cm and the lowest average for strawberry plants in treatment P2 was 9.50. While the number of stowberry tillers aged 8 and 12 weeks after planting (mst) P1 and P2 had no significant effect, meaning that the treatment level had no effect on the number of stowberry tillers.